INVESTIGATING CODE-MIXING AS PERSUASIVE STRATEGIES IN ADVERTISING: A STUDY OF CODE-MIXING IN INDONESIAN COMMERCIAL CONTEXT - Rosmiaty, Rosmiaty; Ratnawaty, Ratnawaty; Muhri, Asriani (ELT Worldwide: Journal of English Language Teaching, 2020)
This study deals with the phenomena of code-mixing with a specific focus on commercial advertising specifically in Indonesian commercial context. It analyzes the use of these techniques in order to produce a persuasive effect in Indonesian today.Â  The objective of this study to investigate the forms of code mixing used in Commercial Advertisement and to shed light on the factors of using code mixing in Commercial Advertisement. The study employs a qualitative descriptive approach by describing about forms and factors of using code mixing in Commercial Advertisement. The research findings revealed six forms of code mixing utilized in Indonesian Commercial Advertisement today. Those are words, phrase, hybrid, repetition, idioms, and clause. The study further showed the factors of using code mixing in Commercial Advertisement. Those were interjection (Inserting sentence fillers or sentence connectors), quoting somebody else, talking about a particular topic, expressing group identity, being emphatic about something and repetition used for clarification.